Clinical Evaluation of Melatonin Alone and in Combination with Pizotifen in the Prophylaxis of Migraine - M.Mohamed Ali, Muqdam; A. Humadi, Salim; N. Al-Jaff, Ashwaq (Iraqi Journal of Pharmaceutical Sciences, 2017)
The treatment of migraine headache targets the neurovascular mechanism and involves the use of serotonin receptor antagonists. Some of these drugs are used for the treatment of acute attacks; while others are effective as prophylactic measures to decrease the duration and frequency of attacks. Pizotifen, a 5-HTA antagonist, is one of the prophylactic drugs for which the clinical use resulted in low outcomes in reducing migraine symptoms. Melatonin, a serotonin derived neurohormone, was reported to exert many functions like sleep induction, anti-inflammatory, neurovascular regulation, cytoprotection and modulation of neurotransmitter release. In the view of the involvement of serotonin in the pathophysiology of migraine and the properties of melatonin, the present study has been conducted to evaluate the effectiveness of melatonin alone or in combination with pizotifen for the improvement of migraine symptoms. The study was conducted on 72 patients, which were under neurologist supervision during the entire period of study. The patients were instructed to avoid any precipitating diet (chocolate, cheese,… etc) and where randomly divided into 4 groups each of 18. The first group was treated with melatonin (3mg, 30 minutes before bed time); the second with pizotifen (0.5mg twice daily); the third with melatonin (at night) and pizotifen (twice daily); and the fourth with placebo (at night). The treatment was continued for 42 days and was followed up and monitored each week. After a month of treatment, the severity, duration and frequency of migraine attacks were recorded using special migraine scoring system.The results revealed that melatonin alone significantly decreased the severity, duration and frequency of migraine attack by 48%, 53% and 45.75%, respectively; while these produced by pizotifen were significantly reduced by 25%, 45.3% and 27.5%, respectively. The effect of pizotifen was generally enhanced by the addition of melatonin and the improvement in migraine symptoms were, severity (59%), duration (62.7%) and frequency (58%). These effects were generally low in placebo treated group and the reduction in severity, duration and symptoms were (12.2%, 20% and 16.2%, respectively). The distribution of patients according to their response as complete or partial was significantly different among treated groups; and within the same group is differ according to the measured parameter suggesting involvement of factors other than treatment in the improvement of migraine symptoms such as psychological state, stress and others.The study has concluded the effectiveness of melatonin alone and in combination with pizotifen as a prophylactic measure in term of reducing the severity, duration and symptoms of migraine headache.Key words: migraine headache, pizotifen, melatonin.